Macroprudential Policy and Labor Market Dynamics in Emerging Economies - Finkelstein Shapiro, Alan (IMF Working Papers; Working Paper ;, 2015)
Emerging economies have high shares of self-employed individuals running owner-only firms who, in contrast to many salaried firms, have little access to formal financing and therefore rely on informal financing (input credit) from other firms. We build a small open economy real business cycle model with labor and financial market frictions where formal credit markets, informal credit, and the structure of the labor market interact. The model successfully replicates the cyclical behavior of sectoral employment, formal credit, and the main macroeconomic aggregates in emerging economies. We show that a countercyclical macroprudential policy that reduces formal credit fluctuations has positive though quantitatively limited effects on consumption and output volatility, but generates larger unemployment fluctuations in response to productivity shocks; the same policy increases labor market and aggregate volatility in response to net worth shocks. The link between input credit and the labor market structure---key for capturing the cyclical dynamics of labor and credit markets in the data---plays a crucial role for these results.